Markers of Atrial Cardiopathy in Severe Embolic Strokes of Undetermined Source - Acampa, Maurizio; Cartocci, Alessandra; Domenichelli, Carlo; Tassi, Rossana; Guideri, Francesca; Lazzerini, Pietro Enea; Martini, Giuseppe (Frontiers in Cardiovascular Medicine, 2022)
Background and Purpose The current definition of embolic strokes of undetermined source (ESUS) seems to be too broad, including strokes due to heterogeneous mechanisms, such as atrial cardiopathy and other occult cardiac conditions, aortic arch plaques, and non-stenosing atherosclerosis, that can be differently associated with clinical stroke severity at the time of presentation. The aim of our study was to assess the possible association between neurological deficit severity and presence of markers of atrial cardiopathy in ESUS. Methods We retrospectively reviewed the medical records of a cohort of 226 ESUS patients (105 M, 121 F), that were divided into two groups according to the severity of neurological deficit (99 mild strokes with NIHSS ≤ 5 and 127 severe strokes with NIHSS >5). The following indices of atrial cardiopathy were evaluated: P wave dispersion, P wave max, P wave min, P wave mean, P wave index, P wave axis, left atrial size. Results Patients with severe ESUS were significantly older (74 ± 12 vs. 67 ± 14 years, P < 0.001) and female sex was prevalent (67 vs. 36%, P > 0.001); they had higher values of P-wave-dispersion (51 ± 14 vs. 46 ± 13, P = 0.01), P-wave-max (131 ± 20 vs. 125 ± 15 ms, P = 0.01), P-wave-index (16 ± 5 vs. 15 ± 5 ms, P = 0.01), left atrial size (20 ± 6 vs. 18 ± 4 cm2, P = 0.01), left atrial volume index (31 ± 14 vs. 27 ± 11 ml/m2, P = 0.04), in comparison with mild ESUS. An abnormal P wave axis was detected more frequently in severe ESUS (21 vs. 9%, P = 0.01). Furthermore, multivariate logistic regression showed that age (OR = 1.21 for each 5-year increase, 95% CI 1.09–1.35), sex (OR = 3.24 for female sex, 95% CI 1.82–5.76) and PWD (OR = 1.32 for each 10-ms increase, 95% CI 1.07–1.64) were the best subset of associated variables for severe ESUS. Conclusions Our findings shed light on specific clinical characteristics of severe ESUS including the presence of atrial cardiopathy that could play a pathogenic role in this subgroup of patients. Searching for atrial fibrillation in these patients is especially important to perform the most appropriate therapy.